Influence of mentoring on the proactive behavior of new employees: moderated mediation effect of agreeableness - Yang, Wenjie; Wang, Yuxue; Choi, Myeongcheol; Li, Yannan (Frontiers in Psychology, 2024)
Objective In recent years, faced with a complex economic development environment and the evolving dynamics of the Chinese workplace, talent has become a precious resource that is invaluable yet scarce for every enterprise. As Generation Z employees have gradually entered the labor market, they contribute new perspectives and energies to various enterprises and pose unique challenges. The traditional step-by-step approach no longer meets the needs of today’s businesses. Companies require more proactive talents to drive superior performance. Individuals with proactive behavior can effectively plan their career paths and are better equipped to fulfill core organizational tasks. Therefore, it is crucial for organizations to effectively mitigate the perceived negative impacts of proactive behavior, encouraging individuals to exhibit more positive proactive actions. Methods Based on the proactive motivation model, this study investigates the effects of mentoring, balanced psychological contract, proactive behavior, and agreeableness on the proactive behaviors of new employees. The research surveyed 417 new employees from Guangdong Province, China, who had graduated within the last three years, with a gender distribution of 49.4% male and 50.6% female. Results Structural Equation Modeling was used for data analysis, and the following results were obtained: First, mentoring positively affected the balanced psychological contract and new employees’ proactive behavior. Second, mentoring positively affected the new employees’ proactive behavior through the balanced psychological contract. Third, agreeableness played a moderating role in the relationship between mentoring and new employees’ proactive behavior, and in the relationship between mentoring and the balanced psychological contracts. Finally, the positive indirect effect of mentoring through the balanced psychological contract on new employees’ proactive behavior is positively moderated by agreeableness. Conclusion The results of this study offer new insights into mentoring research for new employees and provide practical guidance for fostering the balanced psychological contract and proactive behavior among new employees. This research enriches the existing literature on mentoring for new employees by demonstrating the integral roles of agreeableness and a balanced psychological contract in fostering proactive behavior, offering valuable insights for organizational practices aimed at enhancing employee proactivity.